Diretrizes projetuais para jardins terapêuticos: aplicação no Hospital Universitário do Oeste do Paraná (HUOP) - Paris, Barbara Carolina (2021)
This research studies the relationship between man and nature by addressing the beneficial effects of therapeutic gardens on the reestablishment of human health through the contact with nature. A search for theories on the theme was performed. This study firstly presents a broad scenario, in which the authors contextualize hospital humanization and the benefits of therapeutic gardens, and then a more specific scenario, in which they define the term Therapeutic Garden and present case studies. Project guidelines were obtained in order to support the proposition of creating therapeutic gardens at the University Hospital of Western Paraná (HUOP), which is the largest public hospital in the western region of the state of Paraná, Brazil. The research revolves around the question: which project guidelines for therapeutic gardens can be applied in the HUOP? The main goal of this study was to perform a research on therapeutic gardens and verify which project guidelines available in the literature could meet the needs of the hospital. After obtaining these guidelines, preliminary project proposals were made for the creation of therapeutic gardens at the HUOP. In order to formulate these proposals, the authors performed visits to the hospital site to observe its demands, operation and patient flow. The tables containing the guidelines obtained in this study may also serve as a reference for the formulation of projects in other locations.